The risk and return of venture capital - Cochrane, John H. (Journal of Financial Economics, 2005)
This paper measures the mean, standard deviation, alpha, and beta of venture capital investments, using a maximum likelihood estimate that corrects for selection bias. The bias-corrected estimation neatly accounts for log returns. It reduces the estimate of the mean log return from 108% to 15%, and of the log market model intercept from 92% to -7%. The selection bias correction also dramatically attenuates high arithmetic average returns: it reduces the mean arithmetic return from 698% to 59%, and it reduces the arithmetic alpha from 462% to 32%. I confirm the robustness of the estimates in a variety of ways. I also find that the smallest Nasdaq stocks have similar large means, volatilities, and arithmetic alphas in this time period, confirming that the remaining puzzles are not special to venture capital.